Overcoming barriers to crop diversification uptake in Europe: A mini review - Brannan, Timothy; Bickler, Charlotte; Hansson, Helena; Karley, Alison; Weih, Martin; Manevska-Tasevska, Gordana (Frontiers in Sustainable Food Systems, 2023)
Crop diversification (CD) encompasses practices such as extending crop rotation, cover cropping and intercropping practices, and growing minor crops. It has attracted increasing interest because it can produce both private benefits for farmers, including improved crop and soil health, and reduced inputs, and public goods for society, including greater biodiversity, carbon sequestration, and climate resilience. Nevertheless, CD is not widely practiced in Europe. This paper uses a conceptual framework based upon the literature on barriers to agricultural innovation and CD to guide a systematic-like literature review of existing review articles on the barriers to CD in Europe and a review of research from the European Crop Diversification Cluster, comprising six EU research projects. We compare barriers to CD uptake and identify opportunities to accelerate CD uptake, drawing four main conclusions. First, the barriers to CD are influenced by many factors: the specific crop, cropping method, geographical region, the farmer, the supply chain or market, and the institutional environment. Second, the barriers to CD uptake are interconnected and occur at multiple points along the supply chain; addressing barriers to CD uptake therefore requires a simultaneous and coordinated approach. Third, the inclusion of farmers' perspectives in the CD cluster research revealed novel barriers and solutions demonstrating that participatory and transdisciplinary agricultural research is needed to understand the on-farm reality and its influence on CD uptake. Lastly, farmers' decision-making warrants greater attention. The results highlight that farmers' decision-making is unpredictable and likely to focus on utility rather than profit maximization.